Pengaruh Ketelitian Membaca Soal Cerita terhadap Kemampuan Pemecahan Masalah Matematika - Ukti Lutvaidah; Ryan Hidayat (Universitas Indraprasta PGRI, 2019)
The purpose of this research is to find out whether there is influence of accuracy of reading matter of stories against the ability of solving math problems. This research was conducted in the country in JUNIOR 1 Klapanunggal, Bogor 2016/2017 school year where its implementation starts from October 2016 until February 2017. The population in this research is grade VIII and sampelnya taken as a random grade VIII class VIII and Shiva B F with the number of students is 60. This research is descriptive research types and uses of research survey (survey research). To obtain data about the population and sample of researchers using the method documentation, method of observation, and test method. The instruments used in this research is shaped reserved as many as 10 description of problem. The instrument has been tested the validity and reliabiltas first before the instrument is used for research by using correlation Product Moment. This research analysis prerequisite test IE test Kolmogorov-Smirnov using Normality and its homogeneity test using the test F which menghasilakan that the Gaussian data and homogeneous. While the test whose hypotheses using correlation Product Moment. The calculations in this study use Microsoft Excel 2010 and SPSS 20.0. Results of the study show that there are influences accuracy of reading matter of stories against the ability of solving math problems.